Dreaming, fenfluramine, and vitamin C. Issue 6053 (8th January 1977) - Mullen, A; Wilson, C W; Wilson, B P
Abstract : The effect of increasing doses of fenfluramine on dream patterns was studied in 20 patients receiving a reducing diet with or without a controlled dietary intake of vitamin C daily. The dream pattern was unchanged in six patients and dreams disappeared in another who normally dreamed often. In 13 patients dreams increased in frequency and intensity, and in five the dreams assumed frightening proportions. There was a significant straight-line relation between response and the size of the dose. When placebo tablets were given to four patients their dreams disappeared or assumed their pretreatment normal pattern. Absence of vitamin C from the diet did not significantly affect the dream pattern. That fenfluramine has dose-related cerebral effects should be remembered in patients with a history of mental illness.